Variables characterizing probability problems in Spanish secondary education textbooks - Gea, Maria Magdalena; Elgueda-Ibarra, Macarena; Batanero, Carmen (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Despite the importance of problem solving in learning probability, research on the characteristics of probability problems in Spanish textbooks remains limited. This study aimed to examine probability problems in compulsory secondary education textbooks published under recent curricular regulations. Using content analysis, we reviewed two complete textbook series comprising 1,435 problems, focusing on problem fields, meanings of probability, types of sample spaces, contexts, and modes of information presentation. Reliability was ensured by applying and systematically refining categories used in previous studies, as well as by computing the intercoder reliability coefficient. The analysis revealed a strong emphasis on the classical meaning of probability, the use of contexts based on random devices, the predominance of calculation‑oriented problems involving simple or compound experiments, the main use of finite sample spaces, and the provision of information verbally. In addition, exercises prevail over illustrative examples, which are almost always proposed merely to apply the theory. We recommend improving probability problems in Spanish secondary education textbooks by balancing the meanings of probability, diversifying contexts, integrating more experimentation, and increasing the variety of sample spaces and linguistic formats used to present information.